Portrayal of generalized anxiety disorder in YouTube™ videos. (December 2017) - MacLean, Sarah A; Basch, Corey H; Reeves, Rachel; Basch, Charles E
Background: Individuals often search the Internet for information about their medical conditions, such as generalized anxiety disorder (GAD), a common mental health disorder. Aims: To describe the content of the most popular videos on YouTube™ related to GAD. Methods: Videos with at least 50, 000 views in October 2016 were coded for information regarding symptoms, treatments and causes for GAD. Associations of content with factors such as popularity and focus on a personal experience were examined. Results: The search returned 95 videos, which had been collectively viewed 37, 044, 555 times. Most (65%) were uploaded by consumers and 56% were about a personal experience. The most common symptoms mentioned were worry or panic (72%) and social anxiety (46%). Many videos (63%) mentioned at least one treatment, but only 26% mentioned any cause of anxiety. Videos that focused on a personal experience were significantly less likely to mention other phobias ( p = .036), panic disorder ( p = .033) and sleep issues ( p = .016). Conclusion: The majority of the most popular videos on YouTube™ related to GAD were produced by consumers. Improved understanding about what information is available and popular online can assist mental health professionals in aiding their patients and in producing media that is likely to be viewed.